Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.7150/thno.23373
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Sonic Hedgehog Gene Repressed Irradiation-induced Cellular Senescence in Salivary Glands by Promoting DNA Repair and Reducing Oxidative Stress

Abstract: Rationale: Irreversible hypofunction of salivary glands or xerostomia is common in head and neck cancer survivors treated with radiotherapy even when various new techniques are applied to minimize the irradiation (IR) damage. This condition severely impairs the quality of life of patients and can only be temporarily relieved with current treatments. We found recently that transient expression of Sonic Hedgehog (Shh) in salivary glands after IR rescued salivary function, but the underlying mechanisms are not to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 43 publications
1
40
0
Order By: Relevance
“…IR induces persistent DNA damage and cellular senescence in mouse salivary glands, which is a major cause of hyposalivation following IR in mouse models 9 . We have revealed recently that Shh gene transfer in mouse salivary glands inhibited IR-induced cellular senescence by promoting DNA repair and reducing oxidative stress 25 . To determine whether IR induces cellular senescence in pig salivary glands, we performed staining for senescence-associated β-galactosidase (SA-β-gal) on sections of parotid glands collected 5 weeks after IR.…”
Section: Resultsmentioning
confidence: 99%
“…IR induces persistent DNA damage and cellular senescence in mouse salivary glands, which is a major cause of hyposalivation following IR in mouse models 9 . We have revealed recently that Shh gene transfer in mouse salivary glands inhibited IR-induced cellular senescence by promoting DNA repair and reducing oxidative stress 25 . To determine whether IR induces cellular senescence in pig salivary glands, we performed staining for senescence-associated β-galactosidase (SA-β-gal) on sections of parotid glands collected 5 weeks after IR.…”
Section: Resultsmentioning
confidence: 99%
“…In human endothelial cells, GDF-15 promotes radiation-induced senescence through the ROS-mediated p16 pathway, and contribute to the development of atherosclerosis [22]. GDF-15 levels are upregulated under the stress of ischemiareperfusion, and it is important for the generation of reactive oxygen species and the development of senescence [23]. Furthermore, Talia et al showed GDF-15 was associated with aging related impairment and changes, and predicted to be the potential biomarker of cognitive decline [24].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that hAQP1 gene therapy represents an attractive option for the treatment of radiation-induced salivary gland hypofunction, further studies will be necessary to prove its usefulness for the treatment of xerostomia in SS patients. Other gene therapies aiming at transferring sonic hedgehog [ 99 ] or heat shock protein 25 [ 100 ] were shown to both restore AQP5 expression and salivary secretion in irradiated mouse SG [ 101 ]. It still remains to be assessed whether other gene therapies correcting salivary hypofunction in SS mice models are capable of restoring AQP5 expression/localization with SG.…”
Section: Role Of Aqps In the Treatment Of Sjögren’s Syndromementioning
confidence: 99%